Co(ii)-induced giant vibrational CD provides a new design of methods for rapid and sensitive chirality recognition. Issue 54 (15th June 2016) - Berardozzi, Roberto; Badetti, Elena; Carmo dos Santos, Nadia Alessandra; Wurst, Klaus; Licini, Giulia; Pescitelli, Gennaro; Zonta, Cristiano; Di Bari, Lorenzo
Abstract : Enhanced VCD signals correlate easily with the absolute configuration of the α-aminoacid used in our new self assembly and paving the way to easy and sensitive VCD methods. Abstract : We designed a stereodynamic system, where the chirality of the analyte serves as a template for the helicity of the first coordination sphere of Co(ii ). Giant VCD bands induced by Co(ii ) allow the measurement of a completely significant and conclusive VCD spectrum in only a few seconds and/or on minute quantities of the analyte. This paves the way for the development of similar protocols, overcoming the limitations due to weak VCD signals for the assignment of absolute configurations.